Wind in the sails or choppy seas?: People-place relations, aesthetics and public support for the United States' first offshore wind project. (June 2018) - Firestone, Jeremy; Bidwell, David; Gardner, Meryl; Knapp, Lauren
Abstract: The primary social challenge of offshore wind power development may be local community members' struggle to come to terms with the transformation of the ocean. In this study of local residents' perceptions of the first wind power project off the North American coast, we consider whether factors such as aesthetics and place attachment, dependency and identity might serve as barriers or gateways toward an offshore wind power future. Respondents are 420 coastal Rhode Island and Block Island residents who were randomly sampled by mail or internet prior to turbine installation and after project commissioning. Data were analysed using weighted descriptive statistics and multiple imputed regression analysis. 87% of respondents who live in census tracts bordering the coast support or lean toward supporting the project despite paying significantly above-market prices for the electricity generated. Regression models show that support for the project is influenced, at least in part, by general disposition toward wind power and whether a respondent likes the turbines' appearance, with place-related measures having less influence. Descriptions of the wind turbines that resonated with supporters and opponents include respectively, "Symbolic of progress towards clean energy" and "Cause the loss of something intangible, where all you see is the ocean".